1985
DOI: 10.1007/bf00380966
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone suppression and multiple hormonal responses (TSH, prolactin and growth hormone) to TRH in some psychiatric disorders

Abstract: Baseline and TRH-induced changes of thyroid stimulating hormone (TSH), prolactin (PRL), and growth hormone (GH) were measured in 15 healthy control subjects and 63 psychiatric inpatients with DSM-III diagnoses of major depression (n = 19), schizophrenic disorder (n = 20), alcohol dependence (n = 10), and adjustment disorder (n = 14); baseline and postdexamethasone cortisol (CS) were also determined 3-6 days after the TRH-challenge. All patients and controls were women of similar mean age, weight, height, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…9/16 patients treatment resistant Stokes et al (1984) 13 Drug free !9 days. Recently hospitalized chronic SCH Plasma cortisol 08.30 and 22.00 - Banki et al (1985) 20 Drug free for 2 weeks. Recently hospitalized Plasma cortisol 09.00-10.00 - Gattaz et al (1985) 15 Neuroleptic treated, admitted CSF cortisol 09.00-10.00 - Roy et al (1986) 9 Acutely psychotic newly admitted chronic SCH, tested while drug free for 2 weeks and on fluphenazine Plasma cortisol 20.00 No significant differences in drug-free or medicated patients Whalley et al (1986) Long Zhou et al (1987) 48 Drug free for 1 week.…”
Section: Mean Bprs 41mentioning
confidence: 99%
See 1 more Smart Citation
“…9/16 patients treatment resistant Stokes et al (1984) 13 Drug free !9 days. Recently hospitalized chronic SCH Plasma cortisol 08.30 and 22.00 - Banki et al (1985) 20 Drug free for 2 weeks. Recently hospitalized Plasma cortisol 09.00-10.00 - Gattaz et al (1985) 15 Neuroleptic treated, admitted CSF cortisol 09.00-10.00 - Roy et al (1986) 9 Acutely psychotic newly admitted chronic SCH, tested while drug free for 2 weeks and on fluphenazine Plasma cortisol 20.00 No significant differences in drug-free or medicated patients Whalley et al (1986) Long Zhou et al (1987) 48 Drug free for 1 week.…”
Section: Mean Bprs 41mentioning
confidence: 99%
“…Of the 1949 medicated schizophrenia patients, 504 (25.9%) were classified as non-suppressors, suggesting that antipsychotic medications themselves had little effect on DST results. Several studies correlated symptoms such as depressive, negative and positive symptoms with DST outcomes, as Schlesser et al (1980) Mostly inpatients 0/48 (0%) -- Dewan et al (1982) Chronic SCH 6/20 (30%) -No association of post-DEX cortisol with HAM-D or BPRS Rothschild et al (1982) Psychotic inpatients 2/14 (14%) -- Castro et al (1983) Chronic SCH 7/23 (30%) -- Coppen et al (1983) Chronic SCH inpatients 10/46 (22%) -NS associated with negative not positive symptoms Targum (1983) Hospitalized SCH patients 1/14 (7%) - Banki et al (1984) Hospitalized, acutely psychotic 13/34 (38%) -Paranoid SCH < catatonic and hebephrenic Berger et al (1984) Admitted SCH patients 7/23(30%) on admission 4/21 (19%) 7-10 days later -- Hwang et al (1984) SCH inpatients 2/13 (15%) -- Meltzer et al (1984) No details 7/36 (19%) -- Munro et al (1984) Residual SCH outpatients 7/46 (15%) -NS associated with depressive symptoms Nelson et al (1984) Admitted SCH patients 4/14 (29%) -- Rihmer et al (1984) Paranoid SCH 1/20 (5%) -- Sauer et al (1984) Admitted SCH patients 5/20 (25%) -- Sawyer and Jeffries (1984) 20 SCH inpatients 7/20 (35%) -NS associated with melancholic depression not depressed mood Stokes et al (1984) Hospitalized chronic SCH 2/12 (17%) - Banki et al (1985) Recently hospitalized SCH -10/20 (50%) -Baumgartner et al…”
Section: The Dexamethasone Suppression Test In Schizophreniamentioning
confidence: 99%
“…The somewhat arbitrary cutoff levels of "normal responses" were: 5 mUll for TSH, 20 ng/ml for PRL, and 4 nglml for GH. These were defined by our laboratory on the basis of previous experience with a larger number of healthy individuals tested with the same methods, and we also used them in another study (4).…”
Section: Resultsmentioning
confidence: 99%
“…The patients in this study showed a weak, nonsignificant tendency to exhibit some decrease of their plasma levels of a11 three hormones; however, this could be attributed to mere chance. We did not employ maximal stimulation of TRH (15), but preferred to use only 0.2 mg because it could be more sensi• tive to uncover lower pituitary sensitivity, particularly in female patients (4,35).…”
Section: Discussionmentioning
confidence: 99%